Artefacts of history: archaeology, historiography and Indian pasts - Sudeshna Guha (Sage Publications India Pvt. Ltd., 2015)
"Through little known histories of the practices, governance and scholarship of the archaeology of India this book encourages a regard of the manner in which the past is recalled and historicized. It guides us to think afresh of the histories of antiquarianism in South Asia, explore the impetus of collecting and curatorial practices within the scholarship of pre-colonial India, and investigate the diverse historical linkages within the histories of Indian archaeology. It encourages a focus upon issues of historiography, methodology and notions of evidence for responding to the responsibilities and changing needs of the academic scholarship of archaeology"--Provided by publisher.